La desintegración familiar y su repercusión en la formación de valores, amor, respeto, responsabilidad, en las niñas de 6to, y 7mo, año de educación básica de la Escuela Héctor Encalada Sánchez de Puerto Bolívar, período 2012-2013. - Salcedo Suárez, Daniela Marisela (2012)
Family disintegration has become a part of society about the same time that family, becoming a problem that does not respect race, religion, color, social class, economic, nationality, etc.